14-19 year-old basketball players` age- and game-position-specific fitness variation analysis - Kazakov, D. A.; Romanova, A. V.; Eremin, M. V.; Komarov, M. N. (Theory and Practice of Physical Culture, 2021)
Objective of the study was to profile and analyze the age- and game-position-specific physical / technical fitness test data correlations in the 14-19 year-old basketball groups.